Changes in Land Use of Protected Rice Land to Support Food Independence using Remote Sensing Technology - Choir, Miftah; Prayitno, Gunawan; Hasyim, Abdul Wahid; Dzvimbo, Munyaradzi Amire; Mawonde, Albert; Ken, Sugo (Fakultas Teknik Universitas Brawijaya, 2024)
The agricultural sector plays an important role in efforts to deal with food availability. National food independence is one of the programs that is the government's focus. Especially amid the threat of a world food crisis. President Joko Widodo emphasized the need for cooperation to build food independence by developing food according to the characteristics of each region. East Java Province, one of the potential areas, has agricultural land covering an area of 2.29 million Ha. It was recorded that in 2019 it converted 9,597 Ha of agricultural land which was used for warehousing, industry, and property areas. This is because the industrial, residential, and other service sectors are seen as more profitable than agriculture. This paper aims to identify rice fields, plan food crop areas for Protected Rice Fields, and determine the food needs of the population in Malang Regency. Knowing this can be a basis for developing agricultural land policies in Malang Regency. The method used is descriptive quantitative and High-Resolution Satellite Imagery remote sensing techniques in 2022. Existingly, some are in non-rice field land use and are divided into 10 classifications. The results show that in 2022 the rice fields within the protected rice fields area will only be 28,089.24 ha, and outside the protected rice fields area of 1,391.11 ha, capable of producing 335,455.62 tons of rice, it is predicted that this will meet the population's need for rice until 2031. Food crop area plan The spatial plans within the protected rice fields covering an area of 33,436.32 hectares is capable of producing 381,798.62 tons of rice, with this amount of rice production predicted to still be able to meet the population's needs until 2047, when the population's rice needs will be 380,649.69 tons.6.044,82 ha. So recommendations are needed to improve data on raw rice fields and land protection strategies.